A profit-maximization location-capacity model for designing a service system with risk of service interruptions. (December 2016) - Hoseinpour, Pooya; Ahmadi-Javid, Amir
Highlights: A service system design problem with facility-induced interruptions is studied. The system includes facilities of a service provider and its potential customers. Service facilities are modeled using M/M/1 queues with interruptions. A mixed-integer nonlinear programming model is used to determine location, capacity and allocation decisions. An efficient Lagrangian-relaxation algorithm is developed to solve the model. Abstract: This paper considers the design of an immobile service system in which each facility's service process is subject to the risk of interruptions. The location-capacity decisions and allocations are simultaneously made to maximize the difference between the service provider's profit and the sum of customers' transportation and waiting costs. An efficient Lagrangian-based solution algorithm is developed, which solves large-sized instances with up to 50 service facilities and 500 customers in a few seconds. Several sensitivity analyses and managerial insights are presented. The model is also applied to a case study on a logistics network design problem in the zinc mining industry.